2021
DOI: 10.7759/cureus.14348
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Efficacy, Safety, and Tolerability of Abhraloha Compared With Oral Ferrous Ascorbate on Iron Deficiency Anemia in Women: A Randomized Controlled, Parallel-Group, Assessor-Blind Clinical Trial

Abstract: Background and objective Iron deficiency anemia (IDA) is a common condition in women for which ferrous ascorbate (FA) is often prescribed, which can lead to multiple side effects. Abhraloha is an Ayurvedic medicine that has been used for decades in India to treat IDA. In this study, we aimed to evaluate the efficacy and safety of Abhraloha with regard to change in hemoglobin (Hb) levels as compared to the standard treatment using FA in participants with IDA. Materials and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…However, oxidative injury occurs on the cell membrane and blood cell lysis also decreases the level of red blood cell volume (Mohammed et al ., 2021). Similarly, in present study it is observed female rats showed significantly ( P < 0.05) reduction in the level of MCH and MCHC due to the deficiency of iron content which is known as microcytic (Gajbhiye et al ., 2021). In another study, it is reported the level of MCH in male rats (17.9 pg) was significantly ( P < 0.05) increased as compared with female rats (18.1 pg) in another study (Imafidon & Okunrobo, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, oxidative injury occurs on the cell membrane and blood cell lysis also decreases the level of red blood cell volume (Mohammed et al ., 2021). Similarly, in present study it is observed female rats showed significantly ( P < 0.05) reduction in the level of MCH and MCHC due to the deficiency of iron content which is known as microcytic (Gajbhiye et al ., 2021). In another study, it is reported the level of MCH in male rats (17.9 pg) was significantly ( P < 0.05) increased as compared with female rats (18.1 pg) in another study (Imafidon & Okunrobo, 2012).…”
Section: Discussionmentioning
confidence: 99%